The Influence of Shopping Lifestyle, Discount, and Use of Shopee Paylater on Impulsive Buying Behavior in Gen-Z - Putri Novita Sari; Moh. Muklis Sulaeman; Diah Ayu Novitasari; Moh. Heru Budi Santoso (Research Trend in Technology and Management, 2024)
This study aims to analyze the influence of shopping lifestyle, discount , and the use of ShopeePay Later on impulsive buying behavior in Gen-Z. The method used in this study is a quantitative approach with data collection techniques through questionnaires distributed to 276 respondents. The data analysis technique uses multiple linear regression tests with classical assumption tests. The results of the study indicate that shopping lifestyle has a significant effect on impulsive buying , while discounts do not have a significant effect on impulsive behavior. Meanwhile, the use of ShopeePay Later has a significant effect on impulsive behavior in shopping. Simultaneously, these three variables have an effect on impulsive buying . This study is expected to provide insight for e-commerce companies in developing more effective marketing strategies and provide consumers with an understanding of the importance of wiser financial management